Infrastructure planning for climate change adaptation based on land development and surface temperature typology - Rini Erma Fitria; Rahayu Paramita; Werdiningtyas Ratri; Hadiani Rintis (BIO Web of Conferences)
Rapid population growth has led to the development of built-up land in urban agglomeration areas, such as the Surakarta, Boyolali, Sukoharjo, Wonogiri, Sragen, and Klaten (Subosukowonosraten) region. This rapid growth of built-up land is synonymous with the phenomenon of urban sprawl, which contributes to climate change. Consequently, surface temperatures have also increased, indicating the impact of climate change. This research aims to examine the relationship between built-up, surface temperature, and green space to provide a basis for implementing climate change adaptation efforts. Spatial analysis techniques will be employed in this study, utilizing satellite image data from 2000 and 2023 to establish the connection between these variables. The research findings will provide recommendations for infrastructure planning on climate change adaptation.